Can criminologists change the world?: critical reflections on the politics, performance and effects of criminal justice - McAra, Lesley (The British journal of criminology, 2017)
Based on a Scottish case study, this article offers a critical reflection on criminal justice and the impact agenda. It will argue that the pathway to impact requires criminologists to interrogate more fully the inter-relationships between criminal justice as (1) political strategy; (2) institutional performance; and (3) embodied practice. Only by acknowledging the potential for dissonance between these dimensions, it is possible for the discipline to evolve a praxis that is theoretically informed, sensitive to political, spatial and temporal context as well having the highest potential for real-world transformation.